Sociodemographic And Clinical Profile of Mesenteric Lymphadenitis at Tertiary Care Hospital - Trivedi, Miteshkumar R; Sheth, Jenish Y (National Journal of Community Medicine, 2014)
Introduction: This study was conducted to know the etiological factors and distribution of mesenteric lymphadenitis in various age groups and sex, and to study patient’s presentations and manifestations of mesenteric lymphadenitis. Methods: The study reports 100 cases of mesenteric lymphadenitis admitted at Smt. s. c. l. hospital, Ahmedabad, during November 07 to October 09. Results: More than 80% patients were between 1 to 20 years of age. Males are more affected than females, probably due to more prevalent yersinia infection in males. Fever and vomiting are common symptoms along with abdominal pain being constant symptom. In most of cases, aetiological factor remains unknown, although one should look for associated U.R.T.I., appendicitis or worm infestation. Conclusion: Mesenteric lymphadenitis should be considered a differential diagnosis in any patient of 20 years or less, with symptoms of abdominal pain, fever and vomiting. Association of mesenteric lymphadenitis with viral upper respiratory tract infections, worm infestations, tuberculosis and enteric fever suggest that community acquired infections play major role in developing the condition and maintaining proper hygiene and prompt treatment of the underlying condition will decrease the overall occurrence of the condition.